Pengaruh DPK, NPL dan Inflasi Terhadap Penyaluran Kredit Pada PT. Bank Mandiri Periode Tahun 2014 – 2018 - Neria Graca Do Carmo Gomes Pinto; Kompyang Bagiada; Anak Agung Gde Parameswara (Program Studi Ekonomi Pembangunan, Fakultas Ekonomi, Universitas Warmadewa, 2020)
Credit lending activities by banks that contain the risk that can be accounted for by health and banks that support the business, the bank needs to provide matters relating to the credit needed and ensure that those who need credit are received. The purpose of this study was to study DPK, NPL, and simultaneous and partial credit research on lending to Bank Mandiri from 2014 to 2018. The type of data used in this study is quantitative data. The analysis technique used is multiple linear regression analysis. The results obtained indicate that DPK, NPL and the results of a positive and significant assessment of bank lending to PT. Bank Mandiri Period 2014-2018 (sig <0.05). DPK has a positive and significant effect on bank lending to PT. Bank Mandiri Period 2014-2018 (sig <0.05). NPL has a positive and significant impact on bank lending to PT. Bank Mandiri Period 2014-2018 (sig <0.05). Positive and significant inflation towards bank lending at PT. Bank Mandiri for the period of 2014-2018 (sig <0.05).